The effects of the exploitation of natural resources towards risk society construction in Southeast Sulawesi Province, Indonesia - Ambo Upe; Darmawan Salman; Andi Agustang (Journal of Degraded and Mining Lands Management, 2019)
Exploitation of mining everywhere including gold mining in Bombana Regency, Southeast Sulawesi basically always showed two dilemmatic things. On the one hand, it was expected to have a positive contribution in increasing social welfare. On the other hand, it also aroused the risk society. This research aimed to express a variety of risks that happened as the effect of gold mining exploitation in Bombana Regency. This research used qualitative research, a variant case study that was meant to describe profoundly and holistically the effect caused by the mining exploitation. These findings showed that the exploitation of gold mining in Bombana Regency has the impact on the aspect of human and environmental life, namely ecological and socio-economic effects. The above-mentioned complexity of effect constructed a condition called risk society, covering the risk of socio-economic and natural material structures.